Evaluation of Transaction Time Effectiveness in the Implementation of the Multi-Lane Free Flow System (MLFF) on the Trans Sumatra Toll Road - Winanti, Lisa Ayu; Fitriani, Heni; Agustien, Melawati (Fakultas Teknik Universitas Tanjungpura, 2025)
Vehicle queues at toll gates are a significant issue in Indonesia, causing traffic congestion, especially near the toll gates, due to high vehicle volumes. To address this, the Indonesian government plans to implement the Multi-Lane Free Flow (MLFF) system, which allows vehicles to pass without stopping, aiming to reduce congestion and improve traffic efficiency. This study evaluates the feasibility and effectiveness of implementing MLFF at the Keramasan Toll Gate on the Trans-Sumatera Toll Road. The methodology was used quantitatively with an M/M/s queuing model to analyze the current performance of the toll gate service system. Data were collected through field observations, interviews with road users, and secondary data from PT. Jasamarga and the Toll Road Regulatory Agency (BPJT). System performance analysis was conducted by calculating parameters such as average queue length, average time in the system, service rate, and arrival rate. The results show that implementing MLFF can eliminate vehicle transaction times, which previously averaged 8.381 seconds, thus reducing the waiting time in the system to zero seconds. The MLFF system development at the Keramasan Toll Gate is deemed technically and financially feasible, with successful implementation depending on adequate socialization and public support.